The blood pressure in paraplegia. I. - Frankel, H; Michaelis, L; Golding, DR; Beral, V (1972)
The resting B.P.s of patients with complete paraplegia and tetraplegia are recorded at their first check-up. The results are plotted for all the cervicals, each thoracic level and all the lumbar lesions. There is a progressive rise in systolic blood pressure from the cervical down to the lumbar lesions, with a striking linear relationship. The gradient of the regression line is 1·97 and the correlation coefficient is 0·921. The diastolic blood pressure shows a similar linear relationship. The gradient of the regression line is 1·25 and the correlation coefficient is 0·922. © 1972 Nature Publishing Group.